(untitled) (Proceedings of the International Conference on Education, 2023)
Thai youth seem to completely believe green marketing, even when not accompanied by actual efforts to protect the environment, a misleading practice known as greenwashing. This extends to an apparent inability to detect other types of misleading advertising. This study applied media literacy principles to explore the ability of Thai youth to detect false and deceptive advertising, especially greenwashing of products, and to explore connections between specific media literacy skills and ability to detect greenwashing. The study used an online survey with examples of false advertising, deceptive advertising, and greenwashing. Most of the 424 respondents were undergraduate level students. Sahaworakulsak (2018) developed 5 media literacy skills to investigate deceptive advertising in Thailand: Receiving, Understanding, Investigating, Evaluating, and Communication. Proficiency in these media literacy skills was evaluated and compared to the understanding of false and deceptive advertising and greenwashing. The overall mean score of media literacy was moderate at 3.45 out of 5, with the lowest score being Understanding at 2.75, likely influenced by inadequate critical thinking skills taught in high school. Only 21.7% of respondents were aware of greenwashing, out of which approximately a third were unable to then provide an accurate explanation. The most important skill for detecting greenwashing appeared to be the Investigating skill. The preliminary study included students who had taken a course explaining greenwashing, however, preliminary results are consistent with the overall results, suggesting that education about greenwashing had no influence on ability to detect greenwashing. Respondents also demonstrated difficulty distinguishing between completely false and simply deceptive advertising, as expected since Thai has only a single term to describe both types of advertising, and no commonly used term for greenwashing.